2005
DOI: 10.1093/brain/awh554
|View full text |Cite
|
Sign up to set email alerts
|

Differential contributions of prefrontal and temporolimbic pathology to mechanisms of psychosis

Abstract: Common abnormalities within the schizophrenia spectrum may be essential for the pathogenesis of schizophrenia, but additional pathological changes may be required for the development of full-blown schizophrenia. Clarifying the neurobiological similarities and differences between established schizophrenia and a milder form of schizophrenia spectrum disorder would potentially discriminate the pathophysiological mechanisms underlying the core features of the schizophrenia spectrum from those associated with overt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
83
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 71 publications
19
83
0
4
Order By: Relevance
“…This may result from some variation sparing SPD patients from the full development of schizophrenia, an adaptive response to symptoms of the schizophrenia spectrum, or an associated developmental anomaly among other possibilities. Consistent with our findings, Suzuki et al (2005) demonstrated that the prefrontal volumes were largely preserved in SPD in contrast to widespread prefrontal involvement in schizophrenia. It is of interest that in our prior FDG-PET study (Buchsbaum et al 2002) using a task involving verbal working memory in a subgroup of subjects from this study, metabolic rates in BA10 were distinctly higher in SPD patients compared with healthy controls while schizophrenia patients were lowest and this was determined in the same way as in our present study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may result from some variation sparing SPD patients from the full development of schizophrenia, an adaptive response to symptoms of the schizophrenia spectrum, or an associated developmental anomaly among other possibilities. Consistent with our findings, Suzuki et al (2005) demonstrated that the prefrontal volumes were largely preserved in SPD in contrast to widespread prefrontal involvement in schizophrenia. It is of interest that in our prior FDG-PET study (Buchsbaum et al 2002) using a task involving verbal working memory in a subgroup of subjects from this study, metabolic rates in BA10 were distinctly higher in SPD patients compared with healthy controls while schizophrenia patients were lowest and this was determined in the same way as in our present study.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, for the frontotemporal deficit, the schizophreniaspectrum concept is supported with SPD patients intermediate between healthy controls and schizophrenia patients. This spectrum finding suggests that SPD probably represents a milder form of disease along the schizophrenia continuum which is consistent with the review of Dickey et al (Dickey et al 2002a) and other morphometric studies involving SPD and schizophrenia patients Suzuki et al 2005;Takahashi et al 2006b).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, a common result in vulnerable individuals could be in a form of contribution to the 'spiraling distress cycle' (Goldstein and McEwen, 2002;Koob and Le Moal, 2001) depicted in Figure 4, whereby excessive palatable food consumption provoked by its enhanced salience and conditioned learning produces additional deterioration in emotional and behavioral problems, leading to further consumption that may eventually produce a transition from excessive eating to food addiction (Tuomisto et al, 1999). Neuroimaging findings 'Hypofrontality', that is, k in cerebral metabolism and blood flow at baseline and when challenged by cognitive tasks (Weinberger and Berman, 1996), correlated with negative symptoms (Wolkin et al, 1992;Andreasen et al, 1992) 'Hypofrontality' (Volkow et al, 1992;) during withdrawal at baseline and when exposed to natural reinforcers (Garavan et al, 2000), correlated with drug craving (Volkow et al, 2001a) Putative mechanisms k In tonic dopaminergic activity leads to k in tonic glutamatergic activity owing to development-related changes Lieberman et al, 1997;Laruelle, 2000), cortical pyramidal cells may be involved in these changes (Sweet et al, 2004;Lewis et al, 2003) k In basal glutamatergic and dopaminergic activity owing to drug-induced dysmorphisms of the cortical pyramidal cells (Kelley and Schiltz, 2004; Motivational correlates k In initiative towards attainment of natural rewards (Tamminga and Buschbaum, 2004); k in inhibitory control (Suzuki et al, 2005) k In initiative towards attainment of natural rewards; k inhibitory control (Goldstein and Volkow, 2002;) mActivity…”
Section: Neural and Motivational Changes In Schizophrenia And In Sudsmentioning
confidence: 99%
“…As part of the limbic system, the CG is involved in executive function and shares numerous connections with prefrontal cortex and hippocampus (Bush, Luu, & Posner, 2000), two other regions significantly altered in schizophrenia (Gur, Keshavan, & Lawrie, 2007;Suzuki et al, 2005). Moreover, cognitive impairments linked with both of these structures, specifically executive function and working memory, are considered as putative endophenotypes and core features for schizophrenia Mohamed, Paulsen, O'Leary, Arndt, & Andreasen, 1999;Silver, Feldman, Bilker, & Gur, 2003;Snitz, Angus, MacDonald, & Carter, 2006).…”
Section: Introductionmentioning
confidence: 99%